2011
DOI: 10.1051/0004-6361/201116735
|View full text |Cite
|
Sign up to set email alerts
|

Can coronal hole spicules reach coronal temperatures?

Abstract: Aims. The present study aims to provide observational evidence of whether coronal hole spicules reach coronal temperatures. Methods. We combine multi-instrument co-observations obtained with the SUMER/SoHO and with the EIS/SOT/XRT/Hinode. Results. The analysed three large spicules were found to be comprised of numerous thin spicules that rise, rotate, and descend simultaneously forming a bush-like feature. Their rotation resembles the untwisting of a large flux rope. They show velocities ranging from 50 to 250… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 28 publications
5
42
0
Order By: Relevance
“…However, spicules can be considered as Alfvén wave resonant cavities (Hollweg 1981;Leroy 1981) and as Matsumoto & Shibata (2010) claim, the waves of the period around 100−500 s can transport a large amount of wave energy to the corona. In all cases, the question of whether large coronal spicules can reach coronal temperatures remains open -for a discussion from an observational point of view we refer to Madjarska et al (2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, spicules can be considered as Alfvén wave resonant cavities (Hollweg 1981;Leroy 1981) and as Matsumoto & Shibata (2010) claim, the waves of the period around 100−500 s can transport a large amount of wave energy to the corona. In all cases, the question of whether large coronal spicules can reach coronal temperatures remains open -for a discussion from an observational point of view we refer to Madjarska et al (2011).…”
Section: Resultsmentioning
confidence: 99%
“…A number of other studies have also shown that down flows are associated with higher TR temperatures (T ∼ 0.6−1.0 MK) A&A 543, A6 (2012) and high speed up-flows are seen at coronal temperatures (T > 1 MK), e.g. Marsch et al (2004Marsch et al ( , 2008, Bryans et al (2010), , Kamio et al (2011).…”
Section: Introductionmentioning
confidence: 91%
“…They are best seen at the solar limb in strong chromospheric and transition-region (TR) spectral lines such as Hα, Ca ii H & K, Mg ii H & K, C ii and Si iv lines (e.g., Roberts 1945;Matsuno & Hirayama 1988;Nishikawa 1988;Suematsu et al 1995;De Pontieu et al 2007b;Suematsu et al 2008;Sterling et al 2010;Madjarska et al 2011;Pereira et al 2012;Tsiropoula et al 2012;Skogsrud et al 2014Skogsrud et al , 2015Pereira et al 2014;Rouppe van der Voort et al 2015;Pereira et al 2016;Beck et al 2016). Spicule observations have been carried out for about 130 years since they were first reported in 1877 (Secchi 1887).…”
Section: Introductionmentioning
confidence: 99%